Effects of nitrogen fertilization on protein and carbohydrate fractions of Marandu palisadegrass - Leite, Rhaony Gonçalves [UNESP]; Cardoso, Abmael da Silva [UNESP]; Fonseca, Natália Vilas Boas [UNESP]; Silva, Maria Luisa Curvelo [UNESP]; Tedeschi, Luís Orlindo; Delevatti, Lutti Maneck [UNESP]; Ruggieri, Ana Cláudia [UNESP]; Reis, Ricardo Andrade [UNESP] (Springer Nature, 2021)
The effects of nitrogen (N) fertilization levels on protein and carbohydrate fractions in Marandu palisadegrass pasture [Urochloa brizantha (Hochst. ex A. Rich.) R.D. Webster] were investigated in a pasture over five years. The experimental design was completely randomized with four levels of N (0, 90, 180, and 270 kg N ha-1, as urea) for five years, and with three replicates. The study was conducted in a continuously stocked pasture during the forage growing season (December to April) in a tropical region. The effects of N fertilization were similar across the five years. With increasing N fertilization, the concentrations of crude protein (CP) increased from 103 to 173 g kg−1 (P < 0.001), soluble fractions (Fraction A + B1) increased from 363 to 434 g kg−1 of total CP (P = 0.006); neutral detergent fiber (NDF) decreased from 609 to 556 g kg−1 (P = 0.037); indigestible NDF (P = 0.046), potentially degradable neutral detergent fiber (P = 0.037), and acid detergent fiber decreased (P = 0.05), and total digestible nutrient (TDN) increased (P < 0.001). Increasing N fertilization decreased the concentrations of Fraction C (P = 0.014) and total carbohydrates (P < 0.0001), and increased CP:organic matter digestibility (P < 0.01). Concentrations of neutral detergent fiber free of ash and protein (P = 0.003), indigestible neutral detergent fiber (P < 0.001), neutral detergent fiber potentially degradable (P = 0.11), CP (P < 0.001), Fraction A + B1 (P < 0.001), Fraction B2 (P < 0.001), Fraction B3 (P < 0.01), and non-structural carbohydrates differed (P < 0.001) across years. Therefore, N fertilization can be used to increase CP, soluble protein, and TDN.